Northern textiles. A - Varma, J. R. (Jayanth R.); Ghosh, Rahul (London : Indian Institute of Management, Ahmedabad, 2020)
Cases of the Indian Institute of Management, Ahmedabad are prepared as a basis for class discussion. They are not designed to present illustrations of either correct or incorrect handling of administrative problems.© 2020 by Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Strategic planning -- Case studies; Risk management -- Case studies; Textile industry -- Case studies